A gloss to the judgement of 31 may 2019 of the District Court in Częstochowa, 4 U 241/19 - Lewandowski, Piotr (Studia Iuridica Toruniensia, 2020)
The District Court has ruled that a national judge must apply fundamental rights of the EU with precedence over national law, including the Constitution. An independent and effective judicial control, including control of respecting fundamental rights, is main duty of a national court.